(untitled) (Sains Humanika, 2014)
Past studies showed agricultural students in schools were interested to venture into the field of agricultural entrepreneurship. However the realistic figure of those who actually ventured into the field of agricultural entrepreneurship was small and not as expected. Literature has shown that entrepreneurship perseverance had important impact in influencing the decision of an individual to be an entrepreneur. This study seeks to determine the level of perseverance in agricultural entrepreneurship among agricultural science students. This study employed the survey method. Study respondents consisted of 50 students taking Agricultural Science in secondary schools in the state of Selangor. Questionnaire used was adapted from past studies. Data collected were analysed using SPSS. The statistics used were correlation and t-test. Findings from the study indicated studentâ€™s level of agricultural entrepreneurship perseverance was average. There was a significant relationship between agricultural entrepreneurship perseverance and efficacy and characteristics of entrepreneurship.Â The result also illustrated agricultural entrepreneurship perseverance difference between male and female students. The study recommended that agricultural entrepreneurship activities among students be increased to enhance agricultural entrepreneurship perseverance.